Perioperative care in pediatric OTC deficiency and goldenhar syndrome: a case report - Daniela Torres Salazar; Daniela Torres Salazar; Andres Felipe Beltran; Andres Felipe Beltran; Sergio Alzate-Ricaurte; Sergio Alzate-Ricaurte (Frontiers in Pediatrics)
Ornithine transcarbamylase deficiency (OTCD) is an X-linked disorder disrupting the urea cycle in 1 per 56,000 births. Goldenhar syndrome (GS), characterized by craniofacial and vertebral anomalies, is seen in 1 per 3,000–5,000 births. Understanding the pathophysiology and manifestations of both is paramount for developing a perioperative plan. This case report presents a 21-month-old infant with both OTCD and GS undergoing hemifacial malformation correction surgery, the first such report in medical literature. The patient initially presented with lethargy, somnolence, headache, and seizures due to acute liver failure and metabolic acidosis. Diagnosis of OTCD was confirmed through elevated ammonia levels and urine organic acids analysis. The surgical plan involved mandible reconstruction using an autologous costochondral graft. Preoperative management included a low-protein diet and sodium benzoate administration to control ammonia levels. Anesthesia induction and maintenance were carefully managed, with close monitoring of metabolic parameters. The surgery lasted 4 h, during which the patient required transfusion therapy due to easy bleeding. Postoperatively, the patient was monitored in the Pediatric Intensive Care Unit for 48 h before transfer to the general ward. The importance of meticulous preoperative assessment, airway planning, and vigilant intraoperative management in OTCD and GS is underscored. This case highlights the challenges in managing rare comorbidities and emphasizes the need for a multidisciplinary approach. The collaborative effort between specialties led to successful management of this complex case, providing valuable insights for future similar scenarios.